2006
DOI: 10.1088/0960-1317/16/8/018
|View full text |Cite
|
Sign up to set email alerts
|

Creating micro-scale surface topology to achieve anisotropic wettability on an aluminum surface

Abstract: A technique for fabricating micropatterned aluminum surfaces with parallel grooves 30 µm wide and tens of microns in depth is described. Standard photolithographic techniques are used to obtain this precise surface-feature patterning. Positive photoresists, S1813 and AZ4620, are selected to mask the surface, and a mixture of BCl 3 and Cl 2 gases is used to perform the etching. Experimental data show that a droplet placed on the micro-grooved aluminum surface using a micro-syringe exhibits an increased apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
107
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 18 publications
5
107
0
Order By: Relevance
“…They also deduced an equation for the critical inclination angle based on energy considerations to explain qualitatively their observations, whose validity was later questioned by Roura & Fort (2002). Sommers & Jacobi (2006 performed a series of experiments with microgrooved substrates, where they observed that the motion was greatly influenced by the characteristics of the heterogeneities and their orientation relative to gravity. More specifically, they observed reduced critical angles when the groove-spacing is sufficiently small.…”
Section: Introductionmentioning
confidence: 99%
“…They also deduced an equation for the critical inclination angle based on energy considerations to explain qualitatively their observations, whose validity was later questioned by Roura & Fort (2002). Sommers & Jacobi (2006 performed a series of experiments with microgrooved substrates, where they observed that the motion was greatly influenced by the characteristics of the heterogeneities and their orientation relative to gravity. More specifically, they observed reduced critical angles when the groove-spacing is sufficiently small.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can lead to anisotropy in the adhesive properties [24] of gecko feet on surfaces or to anisotropy in wettability in some man-made nanostructured surfaces. [25] The elliptical cross-section of superficial neuromastsstructures that detect water flow on the body surface of fish and amphibians-provides the ability to map the direction of water flow. [13] Motivated by these considerations we have developed a technique, by which we can easily control the geometry of the nanostructures to form both tilted and twisted posts, as well as different 2D symmetries and cross-sectional shapes, using the same original master.…”
mentioning
confidence: 99%
“…Anisotropic wettability has attracted more attentions of the research community. [1][2][3][4][5][6][7][8][9][10][11][12][13] Inspired by the natural microstructure like rice leaf, artificial anisotropic wetting surfaces have been studied recently. Dual-scale micro-nano structures have been prepared by different techniques and their wettability have been studied.…”
Section: Introductionmentioning
confidence: 99%